Digital photography : - Davis, Harold (Wiley, 2005)
The digital camera has revolutionized photography. Sporting events, breathtaking landscapes, the mood of the sea, or a child's eyes as a present is opened-capture whatever fascinates you. Learn touse your images in ways only highly skilled professionals could manage a mere decade ago. With this practical guide in your camera bag, you'll have professional advice at your fingertips to help you get great shots, use all your camera's features, download and enhance your photos, and share them in dozens of creative ways.